2020
DOI: 10.3390/cancers12030537
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Tumor Lactate and Efflux in High-grade Prostate Cancer demonstrated by Hyperpolarized 13C Magnetic Resonance Spectroscopy of Prostate Tissue Slice Cultures

Abstract: Non-invasive assessment of the biological aggressiveness of prostate cancer (PCa) is needed for men with localized disease. Hyperpolarized (HP) 13C magnetic resonance (MR) spectroscopy is a powerful approach to image metabolism, specifically the conversion of HP [1-13C]pyruvate to [1-13C]lactate, catalyzed by lactate dehydrogenase (LDH). Significant increase in tumor lactate was measured in high-grade PCa relative to benign and low-grade cancer, suggesting that HP 13C MR could distinguish low-risk (Gleason sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…3g , Supplementary Table 5 ), as demonstrated by a significant increase in the LDHA / LDHB ratio ( P = 0.006; Supplementary Table 5 ). Increased LDHA and MCT4 expression in aggressive prostate lesions are in agreement with previous studies 36 , 48 , and changes in LDHB have been reported previously 44 , 49 , 50 . However, the role of total LDH expression and individual isoenzyme pattern in the context of clinical hyperpolarised 13 C-MRI has not been elucidated in previous work and provides an important additional measure of metabolism that can be used in future studies.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…3g , Supplementary Table 5 ), as demonstrated by a significant increase in the LDHA / LDHB ratio ( P = 0.006; Supplementary Table 5 ). Increased LDHA and MCT4 expression in aggressive prostate lesions are in agreement with previous studies 36 , 48 , and changes in LDHB have been reported previously 44 , 49 , 50 . However, the role of total LDH expression and individual isoenzyme pattern in the context of clinical hyperpolarised 13 C-MRI has not been elucidated in previous work and provides an important additional measure of metabolism that can be used in future studies.…”
Section: Resultssupporting
confidence: 93%
“…3 ; Supplementary Table 9 ). Overall, these observations are consistent with the known increase in glycolysis in late-stage aggressive PCa 36 , 48 , while also in agreement with reports in which changes in glycolysis could not differentiate GP3 and GP4 disease, suggesting a step-change nature of the emergence of a more glycolytic phenotype in GP5 disease 54 56 . These findings provide further support for the importance of increased tumour epithelial LDH expression with more aggressive disease, which has direct implications for the clinical use of HP 13 C-MRI.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…HP‐NMRS has been successfully used to track metabolite conversion over time in cells cultured in NMR‐compatible bioreactors, providing a useful system for studying cancer cell organoids, 78 tissue slices, 79 or the effects of ionizing radiation in three‐dimensional alginate hydrogel cultures of cancer cells 80 . This method has successfully tracked the concentration and conversion of multiple metabolites in cancer cells, including the conversion of pyruvate to lactate, alanine, and bicarbonate 66,81 and the conversion of αKG to 2‐hydroxyglutarate 71 in cells with mutations in isocitrate dehydrogenase 1 (IDH1) 82 .…”
Section: Methods For Tracking Metabolic Changesmentioning
confidence: 99%